Fibrous dysplasia of maxilla: Report of two cases - Nisha Dua; Neetu Singla; Saloni Arora; Shaveta Garg (Wolters Kluwer Medknow Publications, 2015)
Fibrous dysplasia (FD) is an idiopathic skeletal disorder in which the trabecular bone is replaced and distorted by poorly organized, structurally unsound fibro-osseous tissue. The lesion is classified into two forms: Monostotic (75-80%) and polyostotic. A distinct form of Polyostotic FD, known as McCune-Albright Syndrome, is accompanied by cutaneous pigmentation and sexual precocity, and this occurs almost exclusively in women. Typical radiographic appearance shows an expanded osseous lesion having poorly defined margins covered by a thin "eggshell" cortex and lacking periosteal new bone formation. Here, we are presenting two case reports of FD involving the maxilla.